Criminal Liability of Children in Indonesia: A Review of Age Limits, Implementation of Restorative Justice, and Its Relevance to Islamic Law - Rabbani, Muhammad Ayatullah; Muhshiy, Roshin Abdul; Pasaribu, Muhammad Wildan Hamidi; Ni’am, Asrorun; Rosdiana, Rosdiana (Journal of Legal and Cultural Analytics, 2025)
This study aims to analyze the criminal liability of children in Indonesia with a focus on three main aspects, first, the age limit for criminal liability, second, the implementation of restorative justice in the Juvenile Criminal Justice System (SPPA), and third, its relevance to the principles of Islamic criminal law. The method used is normative law with a qualitative approach, through a literature study of laws and regulations, legal doctrine, and academic literature, as well as a comparative analysis between positive law and Islamic law. The results of the study indicate that the minimum age limit for criminal liability of children is set at 12 years and a maximum of 18 years according to Law No. 11 of 2012, children under 12 years old are subject to correctional measures. The implementation of restorative justice is accommodated through diversion which emphasizes the restoration of social relations and the protection of children's rights, but its implementation still faces obstacles such as regulatory disharmony, limited capacity of officers, and minimal community participation. From the perspective of Islamic law, the responsibility of children is oriented towards intellectual maturity (tamyiz) and puberty, as well as educational punishment through taʿzīr, so there is a meeting point with the restorative concept in positive law.